A pesquisa arqueológica em Quaraí/RS: uma contribuição à identificação do patrimônio local - Toledo, Grasiela Tebaldi (2010)
This dissertation presents a review of archaeological research conducted in the municipality of Quaraí/RS, inserted in the Salamanca Project, developed at the Laboratory of Archaeological Studies and Research, Federal University of Santa Maria (LEPA-UFSM). The research reviewed are presented in the form of dissertations, monographs and some papers, ie research are already developed that rely on important results for the systematization of information about archeology at the southern border of Rio Grande do Sul. This review aims to characterize Quaraí, located in the border region of the state, as a heritage area, in other words, through material culture, analyzed by an archaeological, it is perceived as the region has many heritage that are related spatially and should be disclosed more systematically to the scientific community and regional levels. Concepts, definitions and problems concerning the concepts of cultural heritage are developed contextualizing the discussion of the archaeological heritage of the border west of Rio Grande do Sul. This discussion led to a compilation of the results obtained in the study of archaeological Quaraí, demonstrating how the town can be characterized as a patrimonial territory, since it sought to identify the local heritage through the territorial notion of historical continuity. Thus, it was concluded that the city of Quaraí has great potential archaeological and historical it should be widely disseminated to the local community through the precepts of Public Archeology.